(untitled) (Salud, Arte y Cuidado, 2025)
In order to evaluate the risk of falls and predisposing factors in adults aged 65 years and older from the Fundación Tejiendo Redes outpatient clinic and the Sagrado Corazón de Jesús and Los Peregrinos institutions, Barquisimeto, Lara state, a descriptive cross-sectional study was carried out. After obtaining informed consent, a population of 100 older adults was given a guided interview to collect data such as age, sex, origin, presence of multiple pathologies, polypharmacy and consumption of medications that increase the risk of falls; in addition, the risk of sarcopenia through the SARC-F questionnaire, presence and degree of functional dependence according to the Barthel Index and risk of falls through the Tinetti Scale. The results were: moderate risk of falls 44%, and high risk 29%. In the factors that predispose to falls, medications that increase the risk of falls predominated (74%), followed by dependency (63%), less frequent sarcopenia (30%) and multiple pathologies (22%). Female sex predominated for all the risks of falls. Institutionalized patients had a high risk of falls in 79.3%. Sarcopenia was reported in 62.1% of older adults with a high risk of falls. It is concluded that the most frequent risk of falls found in the population studied was moderate, followed by high risk.